State-of-the-art and trend of emergency rescue communication technologies for coal mine - Qingsong HU; Wei YANG; Enjie DING; Shiyin LI; Binghao LI (Tongxin xuebao)
For the disaster area probing and emergency rescue in a mine,it is of great importance to employ the emergency communication system to communicate with each other,determine the places of trapped miners,and sense current status of disaster area.The hybrid emergency communication architecture model for coal mines was extracted,which was composed of one backbone,multiple branches,several special lines,and some wireless networks as assistance.Four types of emergency communication systems of coal mine were reviewed,namely through-the-air,through-the-wire,through-the-earth and mixed medium type.The key technologies and challenges of these four emergency communication types were analyzed.The research trend was discussed and a new emergency communication mode based on the reconstruction of mine Internet of things was proposed.The main enabling technologies of this new emergency communication mode were analyzed,namely post-disaster reconstruction of mine Internet of things,shifting nodes re-localization after mine disaster,status sensing method of mine disaster area,and data transmission method for post-disaster reconstruction network.